Forestry Seed Development - Maithani, G. P. (Indian Forester, 1992)
The paper describes the present system of (seed procurement in forestry in India and stresses the need for taking up seed development programme, An attempt has been made 10 assess the need for plantation targets and quantity of seed needed. The volume of work in terms of seed quantity, financial implication and size of seed Improvement work bas been estimated, Need for establishing Seed Authorities at the National and State levels has been emphasised and an organisation for the same has been suggesied. Co-ordinating seed development at the subcontinental level has also been discussed by suggesting a coordinating association of SAARC countries. Advantages of seed development programme have been quantified. Seed research and training in seed technology along with creation of training facilities have been stressed upon. Similarly need for seed law, seed manual and law enforcement machinery also have been empbasised.